Pengaruh Profitabilitas dan Sales Growth terhadap Tax Avoidance pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024 - Drajad, Farroqi; Nurani, Khadijah (ARZUSIN, 2026)
Tax avoidance is one of the important issues in taxation studies because it has the potential to reduce state revenue even though it is carried out within the applicable legal framework. Although the factors affecting tax avoidance have been widely studied, studies that specifically discuss the effect of profitability and sales growth on tax avoidance in property and real estate companies during the post-pandemic economic recovery period remain limited. This study aims to analyze the effect of profitability and sales growth on tax avoidance in property and real estate companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study used a quantitative approach with an explanatory design. The research sample consisted of property and real estate companies selected using a purposive sampling technique based on certain criteria during the observation period. The research data consisted of secondary data obtained from companies’ annual financial reports and were collected through the documentation method. Data analysis was conducted using multiple linear regression with the assistance of statistical software. The results show that profitability, proxied by Return on Assets (ROA), has a significant effect on tax avoidance, whereas sales growth has no significant effect on tax avoidance. However, profitability and sales growth simultaneously have a significant effect on tax avoidance. These findings provide empirical support for Agency Theory in explaining the relationship between corporate financial performance and tax avoidance practices. The conclusion of the study affirms that profitability is a more dominant factor in explaining the tendency toward tax avoidance than sales growth in property and real estate companies. The implications of this study include theoretical contributions to the development of taxation literature, as well as practical implications for companies, investors, and tax authorities in understanding the financial factors that influence tax avoidance practices.